2016
DOI: 10.1002/dmrr.2770
|View full text |Cite
|
Sign up to set email alerts
|

Utility of serum lipid ratios for predicting incident type 2 diabetes: the Isfahan Diabetes Prevention Study

Abstract: TG/HDL and TC/HDL ratios were not robust predictors of T2D in high-risk individuals in Iran. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
0
25
2
Order By: Relevance
“…Our finding of a positive association between the TG: HDL‐C ratio and T2D risk is supported by previous studies in Chinese, Iranian, Japanese, and Caucasian men, despite the heterogeneity in statistical methods (studies modeled the TG: HDL‐C ratio as either a continuous variable, a binary variable with a cut‐off point, or in quartiles). However, one prospective study showed a null association . That study was conducted in a group of Iranian people (without diabetes) with a family history of diabetes and participants had much higher BMI and TG: HDL‐C ratios compared with subjects in the present study (mean BMI 29 vs 23 kg/m 2 , respectively; TG: HDL‐C ratio 4.0 vs 1.3, respectively); therefore, the TG: HDL‐C ratio may not predict T2D risk in this specific high‐risk population.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Our finding of a positive association between the TG: HDL‐C ratio and T2D risk is supported by previous studies in Chinese, Iranian, Japanese, and Caucasian men, despite the heterogeneity in statistical methods (studies modeled the TG: HDL‐C ratio as either a continuous variable, a binary variable with a cut‐off point, or in quartiles). However, one prospective study showed a null association . That study was conducted in a group of Iranian people (without diabetes) with a family history of diabetes and participants had much higher BMI and TG: HDL‐C ratios compared with subjects in the present study (mean BMI 29 vs 23 kg/m 2 , respectively; TG: HDL‐C ratio 4.0 vs 1.3, respectively); therefore, the TG: HDL‐C ratio may not predict T2D risk in this specific high‐risk population.…”
Section: Discussioncontrasting
confidence: 65%
“…So far, only a few prospective studies have examined this issue, and the extent to which the TG: HDL‐C ratio is independently related to T2D risk has been variable. Some studies found a positive association, whereas one study showed a null association . Moreover, few studies have explored whether the association is modified by gender and fasting status .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Given the high prevalence of type 2 diabetes and its complications, investigating its etiology, exploring the most modifiable risk factors, and searching for the predictive clinical parameters are of extreme importance for type 2 diabetes prevention and treatment. [35] Apolipoproteins are the primary structural proteins for lipoprotein particles. Apolipoprotein B (ApoB) is the basic apolipoprotein for low density lipoprotein cholesterol (LDL) and apolipoprotein A1 (ApoA1) is the major apolipoprotein for high density lipoprotein cholesterol (HDL).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies suggested that the elevated ApoB to ApoA1 ratio was a more powerful parameter than other lipid fractions for metabolic disorders including type 2 diabetes. [59] However, these studies also assumed that the relationship between ApoB to ApoA1 ratio and type 2 diabetes risk was linear, which was seldom examined in published literatures.…”
Section: Introductionmentioning
confidence: 99%